THU0035 Cytokine profiling of aqueous humor in behÇet's disease patients with active ocular involvement. (15th June 2017) - Soriano, A; Croci, S; Cimino, L; Bonacini, M; Calò, E; Zerbini, A; Parmeggiani, M; Fontana, L; Salvarani, C
Abstract : Background: Behçet's disease (BD) is a systemic inflammatory disorder with unknown etiology. Uveitis and retinal vasculitis occur in 60–80% of patients during the disease course. Previous data on cytokine profiling in aqueous humor (AH) of patients with active BD-related uveitis suggested that both T helper (Th) 1 and Th17 cells are involved in immunopathogenesis [1]. Furthermore, higher levels of Natural Killer T (NKT) cells (CD3+ CD56+) have previously been found in AH of patients with BD-related uveitis as compared to other types of uveitis [2]. However, data on magnitude and patterns of cytokines in BD-related uveitis remain scarce. Objectives: To examine cytokine production as well as frequency of NK and NKT cells in AH from BD patients with active uveitis as compared to patients with active Vogt-Koyanagi-Harada (VKH) disease-related uveitis. Methods: AH from 8 adult patients with BD (1990 ISGB criteria [3]) and active uveitis, and from 7 patients with active VKH were analyzed. Definition of "active" uveitis included ≥2 cells in the anterior chamber (Hogan scale, 1950) and/or 2+ vitritis (Nussenblatt scale, 1990), papillitis, macular edema and retinal vasculitis with active "photo fundus". AH from 5 subjects undergoing cataract surgery were included as controls. Cytokines' concentrations were determined with Bio-Plex Pro-Human cytokine 27-plex assay. Frequency of NK and NKT cells was determined by flow cytometry using anti-CD3, -CD56, -CD16 antibodies. Results: Higher levels of IL-1b, IL-1RA, IL-5, IL-7, IL-6, G-CSF, IFN-g, IP-10, TNF-a IL-8 and MIP1a were found in AH from patients with BD and VKH compared to controls. G-CSF and IFN-g were detected in AH from BD and VKH patients, but not in the control group. Lower levels of GM-CSF were found in BD and VKH patients, while IL-6 levels were 3000-fold increased, as compared to controls. No differences were detected between BD and VKH patients in terms of cytokine levels. However, AH from 4 BD patients showed a peculiar distinct cytokine pattern, when analyzed by unsupervised cluster analysis. Intriguingly, a higher amount of neutrophils/mL was found in AH from these 4 BD cases. Frequency of NKT (CD3+ CD56+) cells was higher in BD patients as compared to VKH, while that of NK (CD56+ CD3 neg ) cells was similar and that of T cells (CD56 neg CD3+) was lower. Finally, no difference was found between NK subsets in terms of proportion of CD16+ cells in both BD and VKH groups. Conclusions: AH of both BD and VKH groups showed increased levels of IL-6, G-CSF and IFN-g, which might suggest their potential role in the immunopathogenesis of these types of endogenous uveitis. However, a distinct cytokine profile able to distinguish the two conditions remains to be identified. Additionally, our preliminary results confirm the previous observation of increased NKT cells levels in BD uveitis as compared to VKH. References: El Asrar A.M., et al. Clin Immunol 2011;139:177–84. Yu H.G., et al. Clin Exp Immunol 2004;137:437–443. International Study Group for Behçet's Disease. Lancet 1990;335:1078–80. Disclosure of Interest: None declared